A System Dynamics Model to Enhance the Indonesian Food and Drug Authority's Approach to Reduce Unauthorized Drug Sales in West Sumatra Province - Putra Gusrianto; Yos Sunitiyoso (Badan Pengawas Obat dan Makanan, 2022)
Indonesia has a high rate of violation of prescription drug sales by unauthorized facilities such as drug stores, retail stores, as well as by doctors and other health professionals. Based on Government Regulation No. 51 of 2009 on Pharmacy Profession, prescription drugs, psychotropics, and narcotics cannot be obtained freely. These drugs can only be obtained with a doctor's prescription and are administered by a pharmacist. Inappropriate prescription drug sales result in drug misuse and irrational use, reducing the quality of drug therapy, increasing morbidity and mortality, wasting resources, reducing drug availability, increasing costs, increasing the risk of side effects, and accelerating the emergence of antimicrobial drug resistance. Between 2018 and 2020, the number of criminal cases handled by the Indonesian FDA (BPOM) related to this issue increased from 8.94% to 14.48%, and the number of violations increased from 39.85% to 68.35% in the Province of West Sumatra. Prescription drug sales violations are complicated, as it involves many factors/variables and parties. This study intends to produce recommendations for reducing violations associated with the sale of prescription drug in West Sumatra Province. This study applied a system dynamic approach to analyze and simulate the variables affecting the sale of prescription drugs at unauthorized facilities. As a result, 31 factors were discovered and 10 scenarios were simulated, showing that the pharmacist's role has a significant impact on the system. Increased public perception and understanding, pharmacists’ and other health workers' responsibilities, and legal enforcement are variables that must be intervened to reduce these violations.